Seasonal scheduling of shellfish collection in the Middle and Later Stone Ages of southern Africa. Issue 128 (March 2019) - Loftus, Emma; Lee-Thorp, Julia; Leng, Melanie; Marean, Curtis; Sealy, Judith
Abstract: This study assesses the seasonal scheduling of shellfish harvesting among hunter-gatherer populations along the southernmost coast of South Africa, based on a large number of serial oxygen isotope analyses of marine mollusk shells from four archaeological sites. The south coast of South Africa boasts an exceptional record of coastal hunter-gatherer occupation spanning the Holocene, the last glacial cycle and beyond. The significance of coastal adaptations, in this region in particular, for later modern human evolution has been prominently debated. Shellfishing behaviors are an important focus for investigation given the dietary and scheduling implications and the abundant archaeological shell remains in numerous sites. Key to better understanding coastal foraging is whether it was limited to one particular season, or year-round. Yet, this has proven very difficult to establish by conventional archaeological methods. This study reconstructs seasonal harvesting patterns by calculating water temperatures from the final growth increment of shells. Results from two Later Stone Age sites, Nelson Bay Cave (together with the nearby Hoffman's Robberg Cave) and Byneskranskop 1, show a pronounced cool season signal, which is unexpected given previous ethnographic documentation of summer as the optimal season for shellfishing activities and inferences about hunter-gatherer scheduling and mobility in the late Holocene. Results from two Middle Stone Age sites, Klasies River and Pinnacle Point 5–6, show distinct seasonal patterns that likely reflect the seasonal availability of resources in the two locations. The Pinnacle Point 5–6 assemblage, which spans the MIS5-4 transition, records a marked shift in shellfishing seasonality at c. 71 ka that aligns with other indications of archaeological and environmental change at this time. We conclude that the scheduling and intensity of shellfishing in this region is affected by a suite of factors, including environmental and cultural drivers, rather than a single variable, such as population growth.